If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(5-2x)=2(5x+1)
We move all terms to the left:
3(5-2x)-(2(5x+1))=0
We add all the numbers together, and all the variables
3(-2x+5)-(2(5x+1))=0
We multiply parentheses
-6x-(2(5x+1))+15=0
We calculate terms in parentheses: -(2(5x+1)), so:We get rid of parentheses
2(5x+1)
We multiply parentheses
10x+2
Back to the equation:
-(10x+2)
-6x-10x-2+15=0
We add all the numbers together, and all the variables
-16x+13=0
We move all terms containing x to the left, all other terms to the right
-16x=-13
x=-13/-16
x=13/16
| 18n-(3n+4)=11 | | 5m+7-3=19 | | 20=-6x+7+1 | | 12x-8x+4x=9+10-3x-7=-6x-2+8x-9x-7+11+4 | | 7x+7=3(x-1) | | h8= 6 | | -5(x+1)=-7x+15 | | 19s-16s=-12 | | 9w-29=-7(w-5) | | 0.08x+8.3=6.14 | | 3.25=1/x-1.2 | | 8x+x-9x+x=17 | | b=7/6 | | 5(v-5)=-3-33 | | 6y-7-3y+3=0 | | 7a-3=3=3-2a | | 4^(3x-2)=5 | | 12s+s-13s+3s+3s=18 | | -40=13t | | -6u-22=-2(u+5) | | 20x-3=36+9 | | -8=-4k | | 12s+s-s13s+3s+3s=18 | | (x+5)=(5x-27) | | 3/4x+6=26-(1/2x+10) | | 3(-2x+4)=-4(2x-6) | | 6(y+2)=-48 | | 2x+x=5=-3x-5x=3 | | 10+3x=25+1x | | 7x+38=-6(5-4x) | | 1/5(-15w-20)+1/2(3-4=) | | 7x+2-3x=10-2x+4 |